Repeated acquisition of conditional discriminations - Moerschbaecher, Joseph M. (1978)
A new technique was developed to study the repeated acquisition of conditional discriminations. Using a discrete trial procedure, pigeons were required to learn during each session a different two-member chain of conditional discriminations. Key color and geometric forms were used as stimuli. After the pigeons had reached a steady state of relearning (40 to 60 sessions), the technique was used to investigate variables that have previously been shown to affect the repeated acquisition of response sequences. Various (0 to 90 seconds) durations of timeout for errors were investigated in Experiment I. The stimulus change associated with a timeout, rather than its duration, was found to be the critical variable in acquisition of the discrimination. Extended training on a single chain was found to reduce total errors across sessions in Experiment II. Extended training (three sessions) did not, however, change the pattern of within-session error reduction. In some cases, extended training facilitated acquisition of a partially reversed discrimination. In Experiment III, color rather than chain position was found to control behavior, for three of the four birds, as the second stimulus dimension in the conditional situation. The results of these experiments replicate and extend previous findings concerning some of the variables that affect the repeated acquisition of response sequences.